Effects of traditional Chinese exercises or their integration with medical treatments on cognitive impairment: a network meta-analysis based on randomized controlled trials - Qiu, Jiadong; Kim, Sungmin (Frontiers in Aging Neuroscience, 2024)
Objective: To summarize and critically evaluate the research on the effects of traditional Chinese exercises and their integration with medical treatments on cognitive impairment. This study assessed the comparative impact of various types of traditional Chinese exercises, both in isolation and in combination with medical treatments. Methods: A systematic search was performed across multiple academic databases, including PubMed, Embase, Web of Science, Cochrane Library, CNKI, Wanfang, and VIP, to identify randomized controlled trials (RCTs) related to cognitive impairment on traditional Chinese exercises and their integration with other treatments. Study quality was assessed using the Cochrane Handbook's Risk of Bias tool. In total, 24 RCTs with 1,808 participants were analyzed. The primary outcome measures were the Montreal Cognitive Assessment (MOCA) and the Mini-Mental State Examination (MMSE). Subgroup analyses were conducted to compare the effects of interventions. Results: The network meta-analysis showed that for MOCA, the combination of Acupuncture and Tai Chi (Aandtaiji) had the most significant effect, followed by Qigong. In terms of MMSE, Tai Chi soft ball exercise (Taijiball) showed the greatest improvement. Conclusions: The combination of traditional Chinese exercises and medical treatments is more effective for improving MOCA scores, while traditional exercises alone yield better results for MMSE scores. Extended practice of Tai Chi and Qigong enhances cognitive outcomes in patients with cognitive impairment.